Expression of an Arabidopsis Aspartate Kinase/Homoserine Dehydrogenase Gene Is Metabolically Regulated by Photosynthesis-Related Signals but Not by Nitrogenous Compounds - Zhu-Shimoni, Judith X. (American Society of Plant Physiologists, 1998)
Although the control of carbon fixation and nitrogen assimilation has been studied in detail, relatively little is known about the regulation of carbon and nitrogen flow into amino acids. In this paper we report our study of the metabolic regulation of expression of an Arabidopsis aspartate kinase/homoserine dehydrogenase (AK/HSD) gene, which encodes two linked key enzymes in the biosynthetic pathway of aspartate family amino acids. Northern blot analyses, as well as expression of chimeric AK/HSD-β-glucuronidase constructs, have shown that the expression of this gene is regulated by the photosynthesis-related metabolites sucrose and phosphate but not by nitrogenous compounds. In addition, analysis of AK/HSD promoter deletions suggested that a CTTGACTCTA sequence, resembling the binding site for the yeast GCN4 transcription factor, is likely to play a functional role in the expression of this gene. Nevertheless, longer promoter fragments, lacking the GCN4-like element, were still able to confer sugar inducibility, implying that the metabolic regulation of this gene is apparently obtained by multiple and redundant promoter sequences. The present and previous studies suggest that the conversion of aspartate into either the storage amino acid asparagine or aspartate family amino acids is subject to a coordinated, reciprocal metabolic control, and this biochemical branch point is a part of a larger, coordinated regulatory mechanism of nitrogen and carbon storage and utilization.